2013
DOI: 10.1186/1745-6673-8-19
|View full text |Cite
|
Sign up to set email alerts
|

“Inclusive working life in Norway”: a registry-based five-year follow-up study

Abstract: BackgroundIn 2001, the Norwegian authorities and major labour market partners signed an agreement regarding ‘inclusive working life’ (IW), whereby companies that participate are committed to reducing sickness absence. Our main aim was to determine the effect of the IW program and work characteristics by gender on long-term (>8 weeks) sickness absence (LSA).MethodsSelf-reported data on work characteristics from the Oslo Health Study were linked to registry-based data on IW status, education and LSA. From 2001–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Within company interventions are therefore considered to be an important mean to reduce disability rates [17]. Earlier Norwegian studies found no effect of working in an IW company [18,19]. However, the dependent variable in these studies was sickness absence, not disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within company interventions are therefore considered to be an important mean to reduce disability rates [17]. Earlier Norwegian studies found no effect of working in an IW company [18,19]. However, the dependent variable in these studies was sickness absence, not disability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependent variable in these studies was sickness absence, not disability. In addition, one of the studies [18] only looked at the effect of working in a company with or without an IW-agreement and not the effect of working in a company with or without preventive workplace interventions. In other words, they have mainly measured the possible effect of working in a company that has access to different public services offered exclusively to IW companies and not the effect of actually having access to preventive workplace interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Five valuable measures have however been proposed in a review on how to measure SA, and cumulative incidence is one of these (17). We chose to use cumulative incidence because the same measure of SA has been used in earlier scienti c papers evaluating the IA Agreement's impact on sickness absence (7,8), thus enabling easier comparisons of results. Our choice was also based on a belief that LSAS could capture changes resulting from the IA interventions, which aim to reduce long lasting and recurring sickness absence spells, and may lead to shorter (< 16 days) and fewer SA spells.…”
Section: Outcome (Long-term Sickness Absence Spells)mentioning
confidence: 99%
“…Two studies showed no impact on SA (7,8), while more recent studies, using causal inference methods, found positive impacts with a higher probability of returning to work (9) and a lower likelihood of receiving a full disability pension (10). These studies are, however, done on selected samples, such as participants on work rehabilitation (9) and older employees aged 50-61 (10), highlighting the need for studies on other samples/cohorts.…”
mentioning
confidence: 98%
“…An RCT assessing the effect of this program in three municipalities found it to be effective in one but not the other municipalities (17). Similarly, the Norwegian Inclusive Working Life Program, taking place for the first time in 2001, was not found to reduce the overall long-term sickness absence rate in companies that had adopted the agreement (18). These somewhat contradictory results may indicate that decisions to prescribe sick leave or look for RTW alternatives may not be easily changed by legislation.…”
mentioning
confidence: 97%